Five-year library development plan for Palaris College in Pangasinan - Baun, Urduja S. (1979)
The Five-Year Library Development Plan of Palaris Colleges in Pangasinan is a study made for the purpose of reorganizing and developing the libraries of the college which have been ineefective and unmanageable for the past many years. It is also intended to serve as an instrument that will contribute to the accreditation of said institution in the near future.